Comparative study on mathematics teaching in professional education curriculum: Brazil and the United States - Gonçalves, Harryson Júnio Lessa [UNESP]; Dias, Ana Lúcia Braz; Peralta, Deise Aparecida [UNESP] (FapUNIFESP (SciELO), 2018)
The article analyses similarities and singularities in the educational systems' organization for Brazil and the United States, their legal benchmarks and curricular frameworks, and highlights in them guidelines concerning mathematics education within vocational education. For this end, we conducted a comparative study between two institutions of vocational education (Brazilian and American), using document analysis and interviews. The paper describes the structure of the two educational systems, and identifies the mathematics configuration as being reassigned with problems and situations from the context of careers. Finally, among other points, we conclude an approach should be used for mathematics education within professional, career, and technical education, which considers applications of mathematics to be embedded in conceptual understanding.
Estudo Comparativo sobre o Ensino de Matemática em Currículos de Educação Profissional Técnica: Brasil e Estados Unidos
Keywords: Career and technical education; Comparative education; Mathematics curriculum; Vocational education; Vocational education and training